Hudud oh hudud: An analysis of the discourse on sharia law in English Malaysian news portals - Muhammad Raqib Mohd Sofian; Safiyyah Ahmad Sabri; Muhamad Zaki Mustafa (Taylor's University, 2026)
Indexed by Scopus